KEPEMIMPINAN KHALIFAH ABU BAKAR AL-SHIDDIQ - Muhammad Rahmatullah (The Pontianak State Institute of Islamic Studies, 2014)
History of the leadership at the time of the Caliph Abu Bakr Al-Shiddiq has a very important meaning in the history of the Islamic Ummat. The reasons for this, among them are: first, the leadership or the Caliph at that time could not be separated from power and if it was not in accordance with the wishes of the people, then it might have caused a conflict; second, a leader is not just a matter of like or dislike, but many factors play an important role such the viewpoint or approach that is used, whether it is his personality, skills, talent, characters or authority he has; third, regardless of the differences of opinion about who is entitled to occupy the office of the Caliphate, which history has proven clearly that Abu Bakr became the First democratically elected Caliph in the history of Islam. The